The safety and efficacy of osimertinib for the treatment of EGFR T790M mutation positive non-small-cell lung cancer - Gao, Xin (Expert Rev Anticancer Ther, 2016)
First- and second-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are the evidence-based first-line treatment for metastatic non-small-cell lung cancers (NSCLCs) that harbor sensitizing EGFR mutations (i.e., exon 19 deletions or L858R). However, acquired resistance to EGFR TKI monotherapy occurs invariably within a median time frame of one year. The most common form of biological resistance is through the selection of tumor clones harboring the EGFR T790M mutation, present in >50% of repeat biopsies. The presence of the EGFR T790M mutation negates the inhibitory activity of gefitinib, erlotinib, and afatinib. A novel class of third-generation EGFR TKIs has been identified by probing a series of covalent pyrimidine EGFR inhibitors that bind to amino-acid residue C797 of EGFR and preferentially inhibit mutant forms of EGFR versus the wild-type receptor. We review the rapid clinical development and approval of the third-generation EGFR TKI osimertinib for treatment of NSCLCs with EGFR-T790M.